Preparation method of transparent ABS grafting latex

CN119775503BActive Publication Date: 2026-10-23WANHUA CHEM GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510002888.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2026-10-23
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

[0003]透明ABS是通过调节连续相MSAN与橡胶相胶粉的折光指数,使两相折光指数相差<0.005,达到在可见光下透明的效果,由于透明ABS良好的抗冲、耐磨、耐化性质,使其在透明材料中拥有广泛的应用,但由于调节折光指数过程中需引入MMA,在通常60-80℃的接枝温度下,会导致MMA水解,乳液PH大幅度降低,从而导致接枝效果不好,乳液稳定性差,需降低接枝乳液的固含量来保证稳定性,制备的透明ABS产品往往生产效率低、性能差且过程中废料较多

Benefits of technology

[0032]本发明的有益效果在于:本发明的胶粉制备方法可以在较低温度下进行接枝聚合,一方面可以降低成本,一方面也减少MMA水解带来的PH降低,提高胶乳稳定性,使胶乳固含量可达50%以上,而且溶胀作用可以提高产品性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a preparation method of transparent ABS grafting latex, which comprises the following steps: (1) adding polybutadiene latex, comonomer 1, emulsifier and water into a reactor and uniformly mixing; (2) adding a first activating agent at a reaction temperature, stirring, fully dispersing the activating agent into the reaction solution and swelling for 0.5-1 hours; (3) adding comonomer 2, an oxidizing agent and a second activating agent into the reactor within 1-5 hours and performing reaction; (4) after the reaction in the third step is completed, adding a third activating agent and continuing to react for 1-4 hours to obtain ABS grafting latex; the latex prepared by the preparation method can effectively improve the stability of the grafting latex, prepare high-solid-content grafting latex, improve production efficiency, control the internal grafting ratio and significantly reduce the haze and b value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of engineering plastics ABS technology, and specifically relates to a method for preparing transparent ABS grafted adhesive powder. Background Technology

[0002] ABS is an acrylonitrile-butadiene-styrene copolymer, a thermoplastic polymer material with high strength, good toughness, and easy processing and molding. It has excellent formability and is mainly used in alloys and plastics.

[0003] Transparent ABS achieves its transparency under visible light by adjusting the refractive indices of the continuous phase MSAN and the rubber phase powder to make the difference between the two phases less than 0.005. Due to its excellent impact resistance, abrasion resistance, and chemical resistance, transparent ABS has a wide range of applications among transparent materials. However, since MMA needs to be introduced during the adjustment of the refractive index, it will cause MMA hydrolysis at the grafting temperature of 60-80℃, resulting in a significant decrease in the pH of the emulsion. This leads to poor grafting effect and poor emulsion stability, requiring a reduction in the solid content of the grafted emulsion to ensure stability. The resulting transparent ABS products often have low production efficiency, poor performance, and a large amount of waste generated during the process.

[0004] In patent CN1177876C, a large amount of sulfonate is added to maintain the balance of the emulsion under pH fluctuations in order to improve the stability of the latex. However, the solid content of the latex is low, and a large amount of electrolyte is introduced in the process, which leads to an increase in wastewater during production. The residual impurities result in higher product haze and B value.

[0005] In patent CN105008406A, a polymerizable emulsifier is used in the grafting process, which improves product stability. However, polymerizable emulsifiers are expensive, and the emulsifier will remain in the polymer, affecting the product's light transmittance and mechanical properties.

[0006] Therefore, providing a method for preparing a transparent ABS grafted latex that is simple to synthesize, has a low polymerization temperature, good emulsion stability, high solid content, and excellent optical properties, and is used to improve the high light transmittance and low haze performance of transparent ABS has become the focus of current research. Summary of the Invention

[0007] This invention provides a method for preparing transparent ABS grafted latex, which can be carried out at low temperature. The method involves a three-stage addition of an activator after high-speed swelling. The latex exhibits high stability and can be used to produce high-solids-content grafted latex with excellent optical properties.

[0008] To achieve the above-mentioned objectives, the present invention is implemented through the following technical solution:

[0009] A method for preparing transparent ABS grafted latex includes the following steps:

[0010] (1) Add polybutadiene latex (PB latex), comonomer 1, emulsifier and water to the reactor and mix well;

[0011] (2) Add the first activator at the reaction temperature, stir, and fully disperse the activator into the reaction solution, allowing it to swell for 0.5-1h;

[0012] (3) Add comonomer 2, oxidant and second activator to the reactor within 1-5 hours to carry out the reaction;

[0013] (4) After the third step of the reaction is completed, add the third part of the activator and continue the reaction for 1-4 hours to obtain ABS grafted latex;

[0014] Optional, (5) add water and coagulant to the reactor, add the ABS grafted latex prepared in step (4) to the coagulant solution, react, then filter, wash and dry to obtain grafted rubber powder;

[0015] In step (1), the emulsifier is one or more of potassium oleate, potassium fatty acid, potassium rosinate, and sodium dodecyl sulfate, preferably potassium oleate. The dry basis mass ratio of the emulsifier to the polybutadiene latex is 0.01:1-0.08:1, preferably 0.03:1-0.05:1.

[0016] Preferably, the comonomers include MMA, polyethylene, and acrylonitrile. Based on a total mass of 100 parts of mixed monomers, the MMA is 50-80 parts, preferably 60-70 parts, the styrene is 10-35 parts, preferably 15-20 parts, the acrylonitrile is 5-15 parts, preferably 10-12 parts, and the mass ratio of comonomer 1 to polybutadiene latex is 0.1-0.4, preferably 0.2-0.3.

[0017] In step (2), the first activator includes a first reducing agent, a first co-reducing agent, and a first complexing agent. The first reducing agent includes one or more of ferrous sulfate, ferrous sulfide, and ferrous hydroxide, preferably ferrous sulfate. The first co-reducing agent includes one or more of glucose, lactose, galactose, and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate. The first complexing agent includes one or more of sodium pyrophosphate, disodium EDTA, and tetrasodium EDTA, preferably sodium EDTA-2.

[0018] In the first activator, the dry basis mass ratio of the first reducing agent to polybutadiene latex is 10. -6 -10 -3 :1, Preferred 10 -5 -10 -4The dry weight ratio of the first reducing agent to polybutadiene latex is 0.0001-0.01:1, preferably 0.001-0.005:1; the dry weight ratio of the first complexing agent to polybutadiene latex is 0.0002-0.02:1, preferably 0.002-0.01:1.

[0019] Step (2) is the high-speed swelling stage, with a stirring linear velocity of 0.5m / s-5m / s, preferably 1m / s-3m / s.

[0020] In step (3), the comonomer 2 includes MMA, styrene, and acrylonitrile. Based on a total mass of 100 parts of comonomer 2, the mass of MMA is 50-80 parts, preferably 60-70 parts, the mass of styrene is 10-35 parts, preferably 15-20 parts, the mass of acrylonitrile is 5-15 parts, preferably 10-12 parts, and the mass ratio of comonomer 2 to polybutadiene latex is 0.5-1, preferably 0.6-0.8.

[0021] In step (3), the oxidant is a peroxide, preferably one or more of cumene hydroperoxide, dicumene hydroperoxide, and tert-butyl hydroperoxide, more preferably cumene hydroperoxide, and the mass ratio of the amount of oxidant to the dry basis of PB is 0.0001:1-0.01:1, preferably 0.02:1-0.05:1.

[0022] In step (3), the second activator includes a second reducing agent, a second co-reducing agent, and a second complexing agent. The second reducing agent includes one or more of ferrous sulfate, ferrous sulfide, and ferrous hydroxide, preferably ferrous sulfate. The second co-reducing agent includes one or more of glucose, lactose, galactose, and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate. The second complexing agent includes one or more of sodium pyrophosphate, disodium EDTA, and tetrasodium EDTA, preferably sodium EDTA-2.

[0023] Preferably, the mass ratio of the second reducing agent, the second co-reducing agent, and the second complexing agent is 0.001-1:0.1-10:0.2-20, more preferably 0.01-0.1:1-5:2-10.

[0024] In step (3), the amount of the second activator is 10%-30% of the mass of the first activator, preferably 15%-25%, the reaction temperature is 5-50℃, preferably 10-40℃, and the reaction time is 1-5h, preferably 2-4h.

[0025] In step (4), the third activator includes a third reducing agent, a third auxiliary reducing agent, and a third complexing agent. The third reducing agent includes one or more of ferrous sulfate, ferrous sulfide, and ferrous hydroxide, preferably ferrous sulfate. The third auxiliary reducing agent includes one or more of glucose, lactose, galactose, and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate. The third complexing agent includes one or more of sodium pyrophosphate, disodium EDTA, and tetrasodium EDTA, preferably sodium EDTA-2.

[0026] Preferably, the mass ratio of the third reducing agent, the third auxiliary reducing agent and the third complexing agent is 0.001-1:0.1-10:0.2-20, more preferably 0.01-0.1:1-5:2-10.

[0027] In step (4), the amount of the third activator is 0.4%-10% of the mass of the first activator, preferably 5%-8%, the reaction temperature is 5-50℃, preferably 10-40℃, and the reaction time is 1-4h, preferably 2-3h.

[0028] In step (5), the ABS grafted latex is uniformly added to the coagulant solution within 1 hour.

[0029] In step (5), the reaction temperature is 75-95℃.

[0030] In step (5), the coagulant is one or more of sulfuric acid, magnesium sulfate, and calcium chloride, preferably calcium chloride, and the dry basis mass ratio of the coagulant to the latex is 1:100-10:100, preferably 3:100-6:100.

[0031] In this invention, in steps (1)-(2), under low temperature and high-speed stirring conditions, the monomers and activators rapidly enter the rubber interior and swell, forming a large number of reaction sites. In step (3), after the addition of the oxidant, the internally swollen latex reacts rapidly to achieve sufficient internal grafting. At the same time, the remaining monomers and emulsifiers, added slowly, form a core-shell structure on the outer layer of the rubber. The further addition of the activator in step (4) further ensures the complete reaction of the monomers. Internal grafting provides sufficient optical path for the rubber, which can improve the optical properties of the product. At the same time, the internal swelling of the rubber also improves the toughening effect of the rubber, thus improving both the optical and mechanical properties of the product.

[0032] The beneficial effects of the present invention are as follows: the method for preparing the rubber powder of the present invention can carry out graft polymerization at a lower temperature, which can reduce costs on the one hand, reduce the pH drop caused by MMA hydrolysis on the other hand, improve the stability of the latex, and make the solid content of the latex reach more than 50%. Moreover, the swelling effect can improve the product performance. Detailed Implementation

[0033] To better understand the technical solution of the present invention, the following embodiments further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.

[0034] Analytical instruments:

[0035] Izod impact strength: CEAST 9050 pendulum impact tester

[0036] Transmittance / Haze: Haze Gard 1 Transmittance / Haze Meter

[0037] Tensile strength and elongation at break: Instron 5966 universal testing machine

[0038] Test method:

[0039] Izod impact strength: Standard ASTM D256

[0040] Tensile strength, elongation at break: Standard ASTM D638

[0041] Light transmittance / haze: ASTM D1003

[0042] Grafting rate test:

[0043] (1) Weigh the dried transparent ABS powder (water content less than 1%, accurate to 0.0001 g, mass is G) into a 100 ml flask, add 50 ml of acetone along the neck of the flask, attach the condenser to the flask, and reflux in a 65℃ constant temperature water bath for 2.0 hours. During this period, do not allow the water bath temperature to exceed 65℃, otherwise bumping may occur.

[0044] (2) Remove the flask and cool it to room temperature. Transfer the solution in the flask to a pre-weighed beaker and let it settle for 4 hours. Remove the supernatant. Place the beaker in a vacuum oven and dry it under vacuum at 65°C until constant weight. Weigh and calculate the dry basis mass as G1.

[0045] The grafted rubber content X (%) is calculated using the following formula:

[0046] Grafted rubber content X = G1 / G * 100%

[0047] In the formula: G1—grafted rubber mass (i.e., total of polybutyl acrylate and grafted SAN), unit: grams;

[0048] G—Sample mass (i.e., ABS grafting powder mass), unit: grams

[0049]

[0050]

[0051] The parts mentioned in Examples 1-5 are molar parts, while the parts mentioned in Examples 6-10 and the comparative examples are mass parts.

[0052] Slag content test:

[0053] (1) Weigh a certain amount of the grafted latex after the reaction is completed, the mass of which is M;

[0054] (2) Filter the grafted latex through a 100-mesh filter. The mass of the filter is ma. After filtration, rinse the filter with pure water until the rinsing liquid is clear. Dry the filter and weigh it, recording its mass as mb. The latex residue content is calculated using the following formula:

[0055]

[0056] Example 1

[0057] (1) Add 100g of PB and 1g of potassium oleate by dry basis to the reactor, adjust the temperature to 20℃, mix evenly, add 25g of mixed monomer-1 of MMA, SM and AN (of which MMA is 70wt%, SM is 20wt%, and AN is 10wt%), stir evenly, and keep the temperature constant for 0.5h.

[0058] (2) Add activator-1 (ferrous sulfate 0.01g, sodium formaldehyde sulfoxylate 1g, sodium EDTA-2 2g), adjust the stirring speed to 5m / s, and stir at high speed for 0.5h;

[0059] (3) Within 1 hour, 25 g of a mixed monomer-2 of MMA, SM and AN (of which MMA is 70 wt%, SM is 20 wt%, and AN is 10 wt%), 1 g of cumene hydroperoxide as oxidant, and 0.001 g of ferrous sulfate, 0.1 g of sodium formaldehyde sulfoxylate and 0.2 g of sodium EDTA-2 were added to the reactor and the reaction was carried out at a constant temperature for 2 hours.

[0060] (4) Add activator-3 (ferrous sulfate 0.0001g, sodium formaldehyde sulfoxylate 0.01g, sodium EDTA-2) and react at a constant temperature for 1h;

[0061] (5) Add 1 kg of water and 2.5 g of sulfuric acid to the reactor, raise the temperature to 60°C, and uniformly add the emulsion after the reaction to the coagulant within 1 hour. After the addition is completed, raise the temperature to 80°C and keep it constant for 3 hours. After the reaction is completed, filter, wash and dry to obtain grafted gum powder.

[0062] Examples 2-6:

[0063] According to the formulations in Table 1, the adhesive powders of Examples 2-6 were prepared respectively, with the remaining reaction conditions and product parameters being the same as those of Example 1. Table 1 shows the raw materials and reaction conditions for Examples 1-6.

[0064] Table 1. Raw materials and reaction conditions for Examples 1-6

[0065]

[0066]

[0067] Comparative Example 1

[0068] A method for preparing transparent ABS involves using polybutadiene as the core and grafting MMA-SM-AN polymer at a reaction temperature of 60-80℃.

[0069] (1) Add 200 parts by weight of polybutadiene latex, 100 parts by weight of water, 1 part by weight of potassium oleate (Qingdao Ruinuo, potassium oleate soap) and 2 parts by weight of potassium persulfate initiator to the reactor and heat to 50°C.

[0070] (2) Add 50 parts by mass of mixed monomers (MMA 70wt%, SM 20wt%, AN 10wt%) to the reactor. At the same time, heat the reactor to 60°C and add the monomers dropwise for 1 hour. After the addition is complete, keep the temperature at 70°C for 0.5 hours. Stop the reaction after the monomers are consumed.

[0071] Comparative Example 2

[0072] (1) Add 200 parts by weight of polybutadiene latex, 100 parts by weight of water, 3 parts by weight of fatty soap (Qingdao Shui Ruocheng Fatty Acid Potassium Soap), and 2 parts by weight of sodium persulfate to the reaction vessel and heat to 50°C.

[0073] (2) Add 100 parts by mass of mixed monomers (MMA 50wt%, SM 35wt%, AN 15wt%) to the reactor. At the same time, heat the reactor to 60°C and add the monomers dropwise for 1 hour. After the addition is complete, keep the temperature at 80°C for 0.5 hours. Stop the reaction after the monomers are consumed.

[0074] Coagulation and Drying: The grafted emulsion prepared in the above examples was coagulated by adding 5% dilute sulfuric acid at 70°C, followed by vacuum filtration and fluidized bed drying (air velocity 180 m / s). 3 After drying at 70℃ for 0.5-1h, ABS grafted powder is obtained.

[0075] ABS resin was prepared by blending and granulation: 24 parts by weight of the above-mentioned ABS grafted powder were mixed with 76 parts by weight of XT-500 (LG Chem), 0.1 parts by weight of antioxidant 1010 (BASF, Germany), 0.1 parts by weight of antioxidant 618 (Panhua Chemical (Shanghai) Co., Ltd.), 0.2 parts by weight of magnesium stearate, and 2 parts by weight of N,N-ethylene bis-stearamide (Shandong Li'ang New Material Co., Ltd.) in a high-speed kneader for 5 minutes. The mixture was then melt-granulated and blended in a twin-screw extruder at 220°C to obtain ABS resin granules. The granules were dried in an oven at 80°C for 2 hours, and then injection-molded for mechanical and optical property testing.

[0076] Examples 1-6 and Comparative Examples 1-2: The prepared ABS powder was agglomerated and dried, then blended and granulated to prepare ABS resin for testing. The properties are shown in Table 2.

[0077] Table 2. Performance test results of the examples and comparative examples.

[0078]

[0079] As shown in Table 2, the latex prepared using the method of this invention during the grafting process can produce highly stable transparent ABS grafted rubber powder. This powder has high solid content, low residue content, improves production efficiency, and enhances performance through swelling structure, thereby improving the optical properties (transmittance and haze) of transparent ABS. This is because, using the preparation method in this patent, transparent ABS can polymerize at a lower temperature during grafting, reducing MMA hydrolysis, resulting in excellent latex stability, high monomer conversion rate, and regular structure. Simultaneously, the swelling technology allows for controllable grafting within the product, increasing the rubber's optical path and improving toughening effect. Transparent ABS prepared using conventional processes suffers from MMA hydrolysis at high temperatures, resulting in low emulsion stability, low grafting rate, and light transmission is easily deflected by the refraction of rubber particles, leading to performance deviations.

Claims

1. A method for preparing transparent ABS grafted latex, characterized in that, Includes the following steps: (1) Add polybutadiene latex, comonomer 1, emulsifier and water to the reactor and mix well; (2) Add the first activator at the reaction temperature, stir, and fully disperse the activator into the reaction solution, allowing it to swell for 0.5-1 h; (3) Add comonomer 2, oxidant, and second activator to the reactor within 1-5 hours to carry out the reaction; (4) After the third step of the reaction is completed, add the third part of the activator and continue the reaction for 1-4 hours to obtain ABS grafted latex; In step (2), the first activator includes a first reducing agent, a first co-reducing agent, and a first complexing agent. The first reducing agent includes one or more of ferrous sulfate, ferrous sulfide, and ferrous hydroxide. The first co-reducing agent includes one or more of glucose, lactose, galactose, and sodium formaldehyde sulfoxylate. The first complexing agent includes one or more of sodium pyrophosphate, disodium EDTA, and tetrasodium EDTA. In step (3), the second activator includes a second reducing agent, a second co-reducing agent, and a second complexing agent. The second reducing agent includes one or more of ferrous sulfate, ferrous sulfide, and ferrous hydroxide. The second co-reducing agent includes one or more of glucose, lactose, galactose, and sodium formaldehyde sulfoxylate. The second complexing agent includes one or more of sodium pyrophosphate, disodium EDTA, and tetrasodium EDTA. In step (4), the third activator includes a third reducing agent, a third auxiliary reducing agent, and a third complexing agent. The third reducing agent includes one or more of ferrous sulfate, ferrous sulfide, and ferrous hydroxide. The third auxiliary reducing agent includes one or more of glucose, lactose, galactose, and sodium formaldehyde sulfoxylate. The third complexing agent includes one or more of sodium pyrophosphate, disodium EDTA, and tetrasodium EDTA. Step (2) is the high-speed swelling stage, with a stirring linear velocity of 0.5 m / s-5 m / s; In step (3), the amount of the second activator is 10%-30% of the mass of the first activator; In step (4), the amount of the third activator is 0.4%-10% of the mass of the first activator.

2. The preparation method according to claim 1, characterized in that, In step (1), the emulsifier is one or more of potassium oleate, potassium fatty acid, potassium rosinate, and sodium dodecyl sulfate; The dry basis mass ratio of emulsifier to polybutadiene latex is 0.01:1-0.08:

1.

3. The preparation method according to claim 2, characterized in that, In step (1), the emulsifier is potassium oleate; The dry basis mass ratio of emulsifier to polybutadiene latex is 0.03:1-0.05:

1.

4. The preparation method according to claim 1, characterized in that, The comonomers include MMA, styrene, and acrylonitrile, with MMA comprising 50-80 parts, styrene 10-35 parts, and acrylonitrile 5-15 parts per 100 parts of total mass of the mixed monomers.

5. The preparation method according to claim 4, characterized in that, The comonomers include MMA, styrene, and acrylonitrile, with MMA comprising 60-70 parts, styrene 15-20 parts, and acrylonitrile 10-12 parts per 100 parts of total mixed monomer mass.

6. The preparation method according to claim 1, characterized in that, The mass ratio of comonomer 1 to polybutadiene latex is 0.1-0.4:

1.

7. The preparation method according to claim 6, characterized in that, The mass ratio of comonomer 1 to polybutadiene latex is 0.2-0.3:

1.

8. The preparation method according to claim 1, characterized in that, In step (2), the first reducing agent is ferrous sulfate; the first co-reducing agent is sodium formaldehyde sulfoxylate; and the first complexing agent is disodium EDTA.

9. The preparation method according to claim 1, characterized in that, In the first activator, the dry basis mass ratio of the first reducing agent to polybutadiene latex is 10. -6 -10 -3 The dry weight ratio of the first reducing agent to polybutadiene latex is 0.0001-0.01:1, and the dry weight ratio of the first complexing agent to polybutadiene latex is 0.0002-0.02:

1.

10. The preparation method according to claim 9, characterized in that, In the first activator, the dry basis mass ratio of the first reducing agent to polybutadiene latex is 10. -5 -10 -4 The dry weight ratio of the first reducing agent to polybutadiene latex is 0.001-0.005:1, and the dry weight ratio of the first complexing agent to polybutadiene latex is 0.002-0.01:

1.

11. The preparation method according to claim 1, characterized in that, Step (2) is the high-speed swelling stage, with a stirring linear velocity of 1m / s-3m / s.

12. The preparation method according to claim 1, characterized in that, In step (3), the comonomer 2 includes MMA, styrene, and acrylonitrile. Based on a total mass of 100 parts of comonomer 2, the mass of MMA is 50-80 parts, the mass of styrene is 10-35 parts, and the mass of acrylonitrile is 5-15 parts. The mass ratio of comonomer 2 to polybutadiene latex is 0.5-1:

1.

13. The preparation method according to claim 12, characterized in that, In step (3), the comonomer 2 includes MMA, styrene, and acrylonitrile. Based on a total mass of 100 parts of comonomer 2, the mass of MMA is 60-70 parts, the mass of styrene is 15-20 parts, and the mass of acrylonitrile is 10-12 parts. The mass ratio of comonomer 2 to polybutadiene latex is 0.6-0.8:

1.

14. The preparation method according to claim 1, characterized in that, In step (3), the oxidant is a peroxide.

15. The preparation method according to claim 14, characterized in that, In step (3), the oxidant is one or more of cumene hydroperoxide, dicumene hydroperoxide, and tert-butyl hydroperoxide.

16. The preparation method according to claim 15, characterized in that, In step (3), the oxidant is cumene hydroperoxide.

17. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of oxidant to polybutadiene dry base is 0.0001:1-0.01:

1.

18. The preparation method according to claim 1, characterized in that, In step (3), the second reducing agent is ferrous sulfate; the second auxiliary reducing agent is sodium formaldehyde sulfoxylate; and the second complexing agent is disodium EDTA.

19. The preparation method according to claim 1, characterized in that, The mass ratio of the second reducing agent, the second co-reducing agent, and the second complexing agent is 0.001-1:0.1-10:0.2-20.

20. The preparation method according to claim 19, characterized in that, The mass ratio of the second reducing agent, the second co-reducing agent, and the second complexing agent is 0.01-0.1:1-5:2-10.

21. The preparation method according to claim 1, characterized in that, In step (3), the reaction temperature is 5-50℃ and the reaction time is 1-5h.

22. The preparation method according to claim 21, characterized in that, In step (3), the amount of the second activator is 15%-25% of the mass of the first activator, the reaction temperature is 10-40℃, and the reaction time is 2-4h.

23. The preparation method according to claim 1, characterized in that, In step (4), the third reducing agent is ferrous sulfate; the third auxiliary reducing agent is sodium formaldehyde sulfoxylate; and the third complexing agent is sodium EDTA-2.

24. The preparation method according to claim 1, characterized in that, In step (4), the mass ratio of the third reducing agent, the third auxiliary reducing agent, and the third complexing agent is: 0.001-1:0.1-10:0.2-20。 25. The preparation method according to claim 24, characterized in that, In step (4), the mass ratio of the third reducing agent, the third auxiliary reducing agent and the third complexing agent is 0.01-0.1:1-5:2-10.

26. The preparation method according to claim 1, characterized in that, In step (4), the reaction temperature is 5-50℃ and the reaction time is 1-4h.

27. The preparation method according to claim 26, characterized in that, In step (4), the amount of the third activator is 5%-8% of the mass of the first activator, the reaction temperature is 10-40℃, and the reaction time is 2-3h.

28. The preparation method according to claim 1, characterized in that, The preparation method further includes step (5), adding water and coagulant to the reactor, adding the ABS grafted latex prepared in step (4) to the coagulant solution, reacting, and then filtering, washing and drying to obtain grafted rubber powder.

29. The preparation method according to claim 28, characterized in that, In step (5), the ABS grafted latex is uniformly added to the coagulant solution within 1 hour.

30. The preparation method according to claim 28, characterized in that, In step (5), the reaction temperature is 75-95℃.

31. The preparation method according to claim 28, characterized in that, In step (5), the coagulant is one or more of sulfuric acid, magnesium sulfate, and calcium chloride.

32. The preparation method according to claim 31, characterized in that, In step (5), the coagulant is calcium chloride.

33. The preparation method according to claim 28, characterized in that, The dry weight ratio of the coagulant to the ABS grafted latex is 1:100-10:

100.

34. The preparation method according to claim 33, characterized in that, The dry weight ratio of coagulant to ABS grafted latex is 3:100-6:100.

Citation Information

Patent Citations

  • Transparent ABS resin and transparent ABS resin composition

    CN105008406A

  • Preparation method of graft polymer and graft polymer

    CN116410408A

  • Preparation method and application of ABS (Acrylonitrile Butadiene Styrene) grafted latex

    CN117567693A